2018
DOI: 10.1371/journal.pcbi.1006283
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised clustering of temporal patterns in high-dimensional neuronal ensembles using a novel dissimilarity measure

Abstract: Temporally ordered multi-neuron patterns likely encode information in the brain. We introduce an unsupervised method, SPOTDisClust (Spike Pattern Optimal Transport Dissimilarity Clustering), for their detection from high-dimensional neural ensembles. SPOTDisClust measures similarity between two ensemble spike patterns by determining the minimum transport cost of transforming their corresponding normalized cross-correlation matrices into each other (SPOTDis). Then, it performs density-based clustering based on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(85 citation statements)
references
References 75 publications
2
83
0
Order By: Relevance
“…Typical border cell classification using the original border score ( Solstad et al, 2008 ) identified only a small fraction of border cells in RSC, as this score is based on the occupancy of a single firing field along a wall and is strongly biased to connected bins ( Figure 1—figure supplement 2A–C ). We thus developed a new model-based approach using a template-matching procedure to classify these border cells in RSC ( Figure 1D–F ), based on Grossberger et al, 2018 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical border cell classification using the original border score ( Solstad et al, 2008 ) identified only a small fraction of border cells in RSC, as this score is based on the occupancy of a single firing field along a wall and is strongly biased to connected bins ( Figure 1—figure supplement 2A–C ). We thus developed a new model-based approach using a template-matching procedure to classify these border cells in RSC ( Figure 1D–F ), based on Grossberger et al, 2018 .…”
Section: Resultsmentioning
confidence: 99%
“…Several additional templates were constructed to assess the effects of behavioral manipulation, adding additional weight in the location of placed objects/walls ( Figure 2E,J ). The EMD distance between a rate map and a template represents the minimal cost that must be paid to transform one distribution into another, with values ranging between zero (identical maps) and one (maximal difference), and is thus a normalized metric of dissimilarity ( Grossberger et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the functional segregation of subnetworks of assemblies may be relevant for understanding how activation of different tectal locations leads to mutually exclusive behaviors [3032]. The assembly activity matrix, obtained from our method, can also be used to identify temporal patterns of assembly activation sequences [33] that might be more relevant than single assembly firing events for understanding tectally-mediated behavior.…”
Section: Discussionmentioning
confidence: 99%
“…HDBSCAN method was used by Rahman (2017) to augment location based services on the Internet (Rahman et al, 2016). It was also used in many biological applications, for instance in clustering of temporal patterns in highdimensional neuronal ensembles (Grossberger, 2018).…”
Section: Clustering Of Countries In Relation To Emissionsmentioning
confidence: 99%